Wanprestasi Dalam Akad Murabahah: (Studi Putusan Pengadilan Agama Mataram No: 0508/Pdt.G/2016/Pa.Mtr) - Alfian Hanggara Putra; Djumardin Djumardin (Private Law, 2023)
Default is led by a debtor's negligence or failure to meet the required obligations determined by a contract while the debtor is not in a force major situation. This research aimed to examine the default occurrence in the Murabahah contract, in the case of consumer default against Bank BRI Syariah Ltd that has been resolved in the religious court of Mataram district, case number 0508/pDT.g/2016/Pa.Mtr. It is proven that the consumer failed to pay his debt which has been arranged under the Murabahah financial contract. This research studied the case by applying the normative legal research method, focusing on the law that is conceptualized as a positive norm to be followed by the society members.